2018
DOI: 10.1155/2018/2796967
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Bulking Agent to Treat Postprostatectomy Urinary Incontinence: A Safety and Effectiveness Pilot Study

Abstract: Objectives To evaluate the safety and effectiveness of the injectable bulking agent Opsys® (Promedon, Cordoba, Argentina) for treating minimal postprostatectomy stress urinary incontinence (SUI). Patients and Methods Single-centre, pilot study on ten male patients with SUI, < 30 g urine loss/ 24 h, more than 1 year after radical prostatectomy. Patients were treated by endoscopic transurethral injections of bulking agent in the presphincteric zone of the urethral submucosa. The results were evaluated using a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Previous studies have shown modest success with urethral bulking injections with satisfaction rates of up to 32% 4 but as low as 10%. 5 The most recent European Association of Urology guidelines state that studies to date are only from small-sample case series, with weak evidence for bulking agents improving quality of life in patients with post-prostatectomy incontinence, and their effects being short-term.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown modest success with urethral bulking injections with satisfaction rates of up to 32% 4 but as low as 10%. 5 The most recent European Association of Urology guidelines state that studies to date are only from small-sample case series, with weak evidence for bulking agents improving quality of life in patients with post-prostatectomy incontinence, and their effects being short-term.…”
Section: Discussionmentioning
confidence: 99%
“…e lack of considerable postoperative results in the selected studies in terms of pad weight does not consent to evaluate the effect of the different groups of devices on this parameter. More data are available in terms of number of pad/day, and in all groups, a significant (P < 0.01) mean reduction was observed after treatment, with the lowest improvement (−2.0 (95% CI −1.43/−2.57) pad/day) in the group of bulking agents and the highest (−5.19 (95% CI Van Uhm (39) Bauer (32) Bauer (31) Bauer (12) Ferro (29) Collado (15) Collado (14) Bauer (43) Renè Yiou (30) Cestari (40) Kim (34) Correira Lima (33) Renè Yiou ( Test of θ i = θ j : Q(0) = -0.00, p = .…”
Section: Advances In Urologymentioning
confidence: 93%
“…Most reported postoperative complications were retention, lower urinary tract infections, and hematuria, while the migration risk remains under investigation. Van Uhm et al 114 utilized MRI to investigate, and they found no correlation between the volume measured and the injected, speculating that paraurethral collagen after RP could be less supportive.…”
Section: Introductionmentioning
confidence: 99%
“…Only elderly patients with mild-to-moderate SUI, not fit for surgery, might find benefit from bulking agents. 110 , 114 …”
Section: Introductionmentioning
confidence: 99%